2003
DOI: 10.1023/a:1021979510860
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previous studies have shown that the bisphosphonates (BP) vary in their damaging effect on the gastric mucosa, and endoscopy scores (erosions or erosions plus ulcers) after 1 and 2 weeks use of BP were significantly lower in H. pylori-positive versus -negative subjects. The mechanism of this damaging effect of BP and the interaction with H. pylori is unknown. As part of a separately reported study of the incidence of gastric damage after 2 weeks of treatment of healthy female postmenopausal volunteers with ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the former studies, most investigations were designed as cross-sectional studies with the exception of 1 case-controlled study, 1 randomized study, and 3 prospective studies. Among 50 selected citations, 32 reports discussed IL-8 as a biomarker for gastric inflammation [65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96], 11 reports described IL-1 as a biomarker for gastric inflammation [66, 69, 77, 82, 92,97,98,99,100,101], and 7 reports focused on TNF-α as a marker for gastric inflammation [71, 77, 81, 82, 90, 91, 102] (fig. 1).…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former studies, most investigations were designed as cross-sectional studies with the exception of 1 case-controlled study, 1 randomized study, and 3 prospective studies. Among 50 selected citations, 32 reports discussed IL-8 as a biomarker for gastric inflammation [65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96], 11 reports described IL-1 as a biomarker for gastric inflammation [66, 69, 77, 82, 92,97,98,99,100,101], and 7 reports focused on TNF-α as a marker for gastric inflammation [71, 77, 81, 82, 90, 91, 102] (fig. 1).…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Namely, successful H. pylori eradication significantly increased antral and juice somatostatin contents, and dramatically decreased IL-8 levels and histological gastric inflammation, suggesting that certain peptide-immune interactions in the gastric mucosa exist in H. pylori infection [70]. Thompson et al [101] reported the association of increased gastric concentrations of mucosal IL-8 and gastric juice IL-1α in H. pylori infection.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…In vitro studies suggest that the mucosal damage is produced through topical irritant effects on the gastric epithelium (60,61). It is also described that BPs are competitively displacing the phospholipids from the mucus gel layer, therefore the mucosal hydrophobic barrier is attenuated and mucosal healing is hindered (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that the mucosal damage is produced through topical irritant effects on the gastric epithelium (60,61). It is also described that BPs are competitively displacing the phospholipids from the mucus gel layer, therefore the mucosal hydrophobic barrier is attenuated and mucosal healing is hindered (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%